Solid Waste Management in the Generation of Economic Income for Informal Recyclers - Aparicio-Ballena, Jorge Alberto,; Guerrero-Campos, , Franklin; Ruiz Gómez, Andrés Alberto,; Chaname-Díaz, Gino,; Luján Johnson, Gladys Lola; Perez-Arboleda, Pedro Antonio (Journal of Ecohumanism, 2024)
This study established the relationship between solid waste management and the generation of economic income for informal recyclers in Chiclayo, Peru. Based on a quantitative, basic, non-experimental and descriptive-correlational approach, with the application of two structured instruments with five ratings on the ordinal Likert scale, duly validated by experts, data were collected from a sample of 300 recyclers through a non-probabilistic sampling by quotas. These data were analyzed using ordinal logistic regression (OLR) and indicated the significant relationship between waste management efficiency and economic income of informal recyclers; acceptable management practices correlated with average income levels, suggesting that improved management could raise the income of these workers; environmental and socioeconomic challenges were also significantly associated with income generation, although health problems arising from poor waste management did not show a direct correlation, their impact on average income levels highlights the importance of addressing these risks. In conclusion, it highlights the need to implement integrated policies that improve waste management, address environmental and socioeconomic concerns, and promote sustainability for informal recyclers.